Social semiotic analysis and efforts to preserve the old mantra of Serdang Malay ethnomedicine in Serdang Bedagai regency, north Sumatra - Rahmat Kartolo; Sutikno Sutikno; Sutarini Sutarini; Nirmawan Nirmawan; Mimi Rosadi; Putri Juwita (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to document and analyze semiotic studies in Serdang Malay Ethnomedicine mantra texts, especially regarding signs and markers which are believed to have spiritual power in Kuala Lama Village, Serdang Bedagai Regency, North Sumatra. This research uses a qualitative approach with field data obtained through observation, in-depth interviews and documentation. The results of this research show that in the old Malay Serdang mantra, there are two main signs, namely the sound or phrase